Analysis Of Millennial Consumer Trust In Environmentally Friendly Products In Medan Denai District, Medan City - Mutahajjid, Zul Azmi; Efendi, Ihsan; Aisyah, Nur (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze millennial consumer trust in environmentally friendly products in the Medan Denai District, Medan City. The independent variables used include product information (X1), product quality (X2), and product price (X3); the mediating variable is consumer trust (Z); and the dependent variable is purchase decision (Y). This research employs a quantitative method with data collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1.1.1. The population of the study consists of 129 individuals, and the sample size was determined using Slovin's formula with a 5% margin of error. The results indicate that product information, product quality, and product price significantly affect consumer trust. Consumer trust, in turn, has the greatest impact on purchase decisions, with an Original Sample (O) value of 0.710 and a T-statistic of 8.875. Product price significantly influences both trust (O = 0.420, T = 3.000) and purchase decision (O = 0.210, T = 2.333), indicating that a reasonable or competitive price can enhance consumer trust and drive purchasing behavior. Similarly, product information significantly affects trust (O = 0.310, T = 2.385) and purchase decision (O = 0.280, T = 2.667). Product quality also affects trust (O = 0.290, T = 2.320) and purchase decision (O = 0.240, T = 2.526), though to a slightly lesser degree. The indirect path analysis shows that consumer trust significantly mediates the relationship between the three independent variables and the purchase decision. Product price has an indirect effect through trust (O = 0.350, T = 2.917), as do product information (O = 0.230, T = 2.091) and product quality (O = 0.260, T = 2.476). These findings highlight that trust is a key factor in driving millennial consumers' decisions to purchase environmentally friendly products, which can be enhanced through pricing strategies, clear product information, and consistent product quality.